Emerging bio-applications of two-dimensional nanoheterostructure materials - Senapati S.; Maiti P. (My University, 2025)
Two-dimensional materials (2DMs) are ultrathin nanomaterials with unique characteristics such as high surface-to-volume ratio, surface charge, shape, high degree of anisotropic, and adjustable chemical functionality. The discovery of graphene and its excellent properties has stimulated researchers to explore new 2D materials and investigate their properties for possible future applications. 2DMs such as graphene-based 2D materials, silicate clays, layered double hydroxides (LDHs), MXenes, transition metal dichalcogenides (TMDs), and transition metal oxides (TMOs) offer enhanced physicochemical and biological functionality. In this chapter, we focus on state of the art of 2DMs considering their synthesis, structural characteristics and biomedical applications as well as recent advancement in this field. © 2020 Elsevier Inc.